Karakteristik Metode Pengambilan Keputusan Kepala Sekolah - Trisharsiwi Trisharsiwi; Yohana Sumiyati (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2020)
This study aims to describe the characteristics of the education budget decision making method in Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta. The research was carried out for six months with the research subjects of the Chairperson of the Ibu Pawiyatan Council, the Head of the Taman Muda Section Mrs. Pawiyatan, the teachers at Taman Muda Ibu Pawiyatan, the treasurer, several staff involved in budgeting, the parents of students who were involved in finding funding sources, and a person who is always critical in making decisions and budgeting, both at the Ibu Pawiyatan Council level or at the Taman Muda Ibu Pawiyatan section. The research data were collected by in-depth interviews, observation and documentation. The research data were analyzed by using the data analysis technique version of Huberman and Miles which consists of data reduction, data presentation, and conclusion drawing. The results showed that the characteristics of the principal's education budget decision-making method were selective minority and seniority, as well as scientific authoritarian.